Synthesis and in vitro Biological Evaluation of a Series of 5-Benzylidene Derivatives of Rhodanine-Sulfonylurea Hybrid as a Novel Class of α-Glucosidase Inhibitors - Suresh, Asha Nandini; Anak Luang, Adam Sammuel; Yet Ling, Michelle Chai; Selvam, Thishaa Nair; Avupati, Vasudeva Rao (Asian Journal of Chemistry, 2024)
A novel rhodanine-sulfonylurea hybrid (C) has been prepared based on the isocyanate-amine reaction conditions in the first step and its 5-benzylidene analogues (C1-C13) were synthesized using Knoevenagel reaction conditions as the subsequent step. The physical and spectral characterization of all the synthesized compounds (C-C13) was performed using FT-IR, 1H NMR and HR-ESI-MS spectral methods. All compounds were subjected to in vitro α-glucosidase enzyme inhibitory properties at 100 µM concentration. The results were compared with a standard drug, voglibose, also tested at the similar concentrations. The bioassay results revealed that the intermediate compound C was more potent with a percentage inhibitory activity of 64.86%, which is relatively better than the series of 5-benzylidene analogues (C1-C13) synthesized from the intermediate C. This clearly displayed that substitution at position-5 on the rhodanine ring of intermediate C is not a favourable substitution to enhance the bioactivity; however, one of the derivative compounds, C12, has exhibited potency of 58.32%, which is close to the compound C. It is significant that both the intermediate C and compound C12 displayed better potency compared to the standard voglibose, with percentage inhibition recorded at 37.75%. The additive or synergistic potential of the bioactive pharmacophore tosylurea, which was earlier established, tolerated the rhodanine ring substitution towards retaining the α-glucosidase inhibitory properties.